(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: Patriotism is an essential aspect of moral and civic education that shapes the identity and values of young individuals. In primary and secondary schools, teaching patriotism not only fosters a sense of national pride but also encourages active participation in the community and the development of responsible citizens. This paper explores various methods for teaching patriotism in the classroom, focusing on the role of history, culture, literature, and extracurricular activities. Additionally, it examines the importance of teachers as role models and the integration of national symbols, traditions, and values into the curriculum. By combining theoretical approaches with practical strategies, this paper aims to provide educators with effective tools for instilling a deep sense of patriotism in students from an early age, promoting unity and respect for the nation’s heritage.